Artefactual Suboptimal Fixation Effect to Nuclear Staining on Erythrocytes of Lutjanus kasmira (Forsskål 1775) - Huu-Quyet Do; Van-Thanh Vo; Nguyen Thi Le-Na; Hoang Thi Thuy-Duong (Bogor Agricultural University, Indonesia, 2023)
This research presents the unusual staining characteristic of the teleosts red blood cells–the common bluestripe snapper Lutjanus kasmira, caught at Toc Tan (Allison) Reef, Truong Sa Archipelago, Vietnam, due to side effects of the delayed staining procedure. In addition to the quantitative data measured, the results of microscopic image research showed that, on slides performed with the delayed Romanovsky staining procedure using Giemsa dye, the cell